Effects of photobiomodulation therapy in patients diagnosed with temporomandibular dysfunction of Coari municipality: case report (Research, Society and Development, 2022)
Temporomandibular dysfunction (TMD) is defined as a group of heterogeneous disorders and clinical problems that involve the masticatory muscles, temporomandibular joint (TMJ), and other structures of the orofacial region. Among the non-invasive therapeutic modalities, photobiomodulation therapy (PBMT) has been widely used in the treatment of musculoskeletal disorders because of its positive effects in reducing pain, inflammation and optimizing tissue repair processes. The aim of this study was to analyze the effects of PBMT in the treatment of TMD, aiming at reducing pain and improving joint range of motion, as well as to compare muscle condition before and after irradiation by measuring localized temperature. This is a case report, with 2 participants. Pain was assessed by visual analog scale (VAS), joint range of motion by pachymeter, and temperature by thermography. They were evaluated before and after a protocol of 9 sessions of TFBM with low power laser (GaAs) with the following parameters: wavelength 790 nm, average power density 0.12mWcm2, energy density 6J/cm2. There was a reduction in pain and an increase in TMJ joint range of motion. In addition, PBMT was not shown to have an effect on facial temperature.